2008
DOI: 10.3141/2055-16
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adverse Weather on Traffic Crashes

Abstract: identify relevant studies by a systematic search and then use effect size standardizing on each study result. In addition, this approach corrects sampling error and other artifacts, and it can present an estimate of the total effect with minimized subjectivity (5). Further, since different studies might be influenced by methodologies, time span, and regions, hierarchy meta-analysis has been applied using these factors as grouping variables. Separate analyses are conducted for each group.The process used in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(107 citation statements)
references
References 19 publications
4
98
1
Order By: Relevance
“…Despite the fact that the link between weather conditions and traffic crashes is far from clear (Edwards, 1998) there are some common findings and suggestions. In regards to driving in rainy conditions it has been shown that there is an increased risk of a crash in wet rather than dry weather (Brodsky and Hakkert, 1988) and in a recent metaanalysis it was found that crash rates in rain are increased up to 71% (Qiu and Nixon, 2008). Rain conditions obviously make driving more dangerous due to the impact of decreased friction on stopping distances and handling.…”
Section: Night and Rain Drivingmentioning
confidence: 98%
“…Despite the fact that the link between weather conditions and traffic crashes is far from clear (Edwards, 1998) there are some common findings and suggestions. In regards to driving in rainy conditions it has been shown that there is an increased risk of a crash in wet rather than dry weather (Brodsky and Hakkert, 1988) and in a recent metaanalysis it was found that crash rates in rain are increased up to 71% (Qiu and Nixon, 2008). Rain conditions obviously make driving more dangerous due to the impact of decreased friction on stopping distances and handling.…”
Section: Night and Rain Drivingmentioning
confidence: 98%
“…For example, according to a crash causation survey released by the US National Highway Traffic Safety Administration (NHTSA) in 2015 [2,3], drivers are to be criticised for 94% of crash cases. Apparently, the 94% of such accidents are also related to other causes from common experience, such as road alignment [4][5][6], traffic sign [7][8][9], and weather condition [10][11][12]. Therefore, the existing road accident statistics cannot fully reveal the causes, and traffic…”
Section: Introductionmentioning
confidence: 97%
“…Symons and Perry [53] found that wet roads or raining is increasing the probability of traffic accidents which can reach up to 70 percent. Similarly, Qiu and Nixon [11] found that rain can increase the crash rate by 71% and the injury rate by 49%. This coincides with the results found in this research, which indicate that rainfall is associated with traffic accidents that had serious injuries and heavy property damage.…”
Section: Weather Conditionmentioning
confidence: 99%
“…Andrey et al (2001) show that snow substantially increases the risk of collisions and injuries relative to dry weather control periods. For the United States, reports state that winter conditions increase the crash rate by 84 % and the injury rate by 75 % (Qiu 2007). Strong et al (2010) found that adverse winter weather reduces traffic speeds and increases crash frequencies, while the number of fatal crashes actually decreases.…”
Section: Some Evidence From Literaturementioning
confidence: 99%